2010
DOI: 10.1021/la102211d
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Formation and Microphase Behavior of Amphiphilic ABC Triblock Copolymers in Selective Solvents: A Monte Carlo Study

Abstract: Using Monte Carlo simulation, we studied the vesicle formation and microphase behavior of ABC triblock copolymers in selective solvent for A and C blocks. Simulation results show that the hydrophilicity of Blocks A and C determines not only the vesicle formation but also the microphase behavior. If Blocks A and C are of equal length, then Block A (with lower hydrophilicity) is likely to aggregate on the inner surface, whereas Block C (with higher hydrophilicity) tends to move to the outer surface, forming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…In addition to extensive experimental investigations, theoretical studies and computer simulations provide powerful tools for studying the self-assembly of block copolymer solutions. [29][30][31][32][33][34][35] The majority of investigations have focused on the effect of the properties of the copolymer or selective solvent on aggregate morphologies, such as copolymer composition, volume fraction, configuration, and selectivity strength. Using simulated annealing, Sun et al studied the self-assembly of diblock copolymers in selective solvents (using only one type of solvent).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to extensive experimental investigations, theoretical studies and computer simulations provide powerful tools for studying the self-assembly of block copolymer solutions. [29][30][31][32][33][34][35] The majority of investigations have focused on the effect of the properties of the copolymer or selective solvent on aggregate morphologies, such as copolymer composition, volume fraction, configuration, and selectivity strength. Using simulated annealing, Sun et al studied the self-assembly of diblock copolymers in selective solvents (using only one type of solvent).…”
Section: Introductionmentioning
confidence: 99%
“…Using Monte Carlo simulations, Jiang's group found that the hydrophilicity of blocks A and C was the key parameter for vesicle formation and the microphase behavior of ABC triblock copolymers in selective solvents for A and C blocks. 31 For an A-B-C-A tetrablock copolymer in selective solvents, the chain length ratio and hydrophobicity of blocks B and C were key factors in determining the hydrophobic layer structure of the vesicles. 32 In their study on asymmetric vesicles constructed from an AB/CB diblock copolymer mixture in a selective solvent for A and C blocks, they found that the vesicle structure sequence depends on the composition of the mixture, the chain length of the hydrophilic block, and the solution pH.…”
mentioning
confidence: 99%
“…[6][7][8] Up to now, most of the polymeric vesicles are generated from the self-assembly of linear block copolymers, and are denoted as polymersomes. These simulation works are mainly focused on four parts: the first part is about the vesicle self-assembly from block copolymers [9] and dendrimers; [10] the second part is related to the mixtures between lipids, homopolymers, block copolymers, dendrimers, or nanoparticles; [11] the third part is about the fusion, fission, and rupture of vesicles, and the interaction between the vesicle and the membrane; [12] and the forth part is about the microphase separation behavior and shape transformations of vesicles. The simulation work can be divided into atomistic scale simulations and mesoscopic scale simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used simulation techniques are molecular dynamics (MD), Monte Carlo (MC), Brownian dynamics (BD), dissipative particle dynamics (DPD), selfconsistent field theory (SCFT), and density functional theory (DFT). These simulation works are mainly focused on four parts: the first part is about the vesicle self-assembly from block copolymers [9] and dendrimers; [10] the second part is related to the mixtures between lipids, homopolymers, block copolymers, dendrimers, or nanoparticles; [11] the third part is about the fusion, fission, and rupture of vesicles, and the interaction between the vesicle and the membrane; [12] and the forth part is about the microphase separation behavior and shape transformations of vesicles. [13] These theoretical works have greatly broadened our knowledge on polymersomes.…”
Section: Introductionmentioning
confidence: 99%
“…30 To complement the simulation work, self-consistent field theory (SCFT) has been used to study the thermodynamics of triblock polymers in dilute solution. Theory and simulations can provide the desired insights.…”
Section: Introductionmentioning
confidence: 99%